ANALISIS PENEGAKAN HUKUM TERHADAP PELAKU TINDAK PIDANA KEKERASAN SEKSUAL (STUDI KASUS PUTUSAN NOMOR 47/PID.SUS/2023/PN.GST) - Dedi Parna Putra Waruwu; Khomaini Khomaini; Dewi Robiyanti (Faculty of Law, Khairun University, 2026)
Sexual violence is a complex form of human rights violation because it involves legal, social, cultural, and psychological aspects. This study aims to analyze law enforcement against perpetrators of sexual violence based on Law No. 12 of 2022 with a case study of Decision No. 47/Pid.Sus/2023/PN.GST. In addition, this study also identifies the factors that cause sexual violence, the motives of the perpetrators, and the impacts experienced by the victims, including the implementation of restitution. The method used is qualitative research with a normative and empirical juridical approach. The theories used include Soerjono Soekanto's theory of law enforcement, Gustav Radbruch's theory of legal certainty, and the theory of victim protection. The results of the study show that although Law No. 12 of 2022 provides a progressive legal basis, its implementation faces challenges in the form of limited understanding by officials, patriarchal culture, minimal access to recovery for victims, and weak restitution mechanisms.